2012
DOI: 10.1021/jm300978h
|View full text |Cite
|
Sign up to set email alerts
|

Multitarget-Directed Benzylideneindanone Derivatives: Anti-β-Amyloid (Aβ) Aggregation, Antioxidant, Metal Chelation, and Monoamine Oxidase B (MAO-B) Inhibition Properties against Alzheimer’s Disease

Abstract: A novel series of benzylideneindanone derivatives were designed, synthesized, and evaluated as multitarget-directed ligands against Alzheimer's disease. The in vitro studies showed that most of the molecules exhibited a significant ability to inhibit self-induced β-amyloid (Aβ(1-42)) aggregation (10.5-80.1%, 20 μM) and MAO-B activity (IC(50) of 7.5-40.5 μM), to act as potential antioxidants (ORAC-FL value of 2.75-9.37), and to function as metal chelators. In particular, compound 41 had the greatest ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(85 citation statements)
references
References 33 publications
1
82
0
Order By: Relevance
“…A number of studies in patients with AD have shown that up-regulated MAO is a reasonable biomarker for the disease (Sparks, Woeltz, & Markesbery, 1991;Oreland & Gottfries, 1986;Sherif, Gottfries, Alafuzoff, & Oreland, 1992) with levels significantly up-regulated to as much as 30% (Zellner et al, 2012). Such elevated and up-regulated levels of MAO may contribute to the oxidative stress and cognitive impairment through neuroinflammation as MAO generates hydrogenperoxide and ammonia which are among the main culprits contributing to the formation of amyloid plaques (Huang et al, 2012;Zheng, Fridkin, & Youdim, 2012). This study is expected to deliver results by December 2016.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 82%
“…A number of studies in patients with AD have shown that up-regulated MAO is a reasonable biomarker for the disease (Sparks, Woeltz, & Markesbery, 1991;Oreland & Gottfries, 1986;Sherif, Gottfries, Alafuzoff, & Oreland, 1992) with levels significantly up-regulated to as much as 30% (Zellner et al, 2012). Such elevated and up-regulated levels of MAO may contribute to the oxidative stress and cognitive impairment through neuroinflammation as MAO generates hydrogenperoxide and ammonia which are among the main culprits contributing to the formation of amyloid plaques (Huang et al, 2012;Zheng, Fridkin, & Youdim, 2012). This study is expected to deliver results by December 2016.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 82%
“…Elevations in MAOA in Alzheimer neurons have been linked to increase in neurotoxic metabolites and neuronal loss. Compelling studies have shown that the involvement of MAO in AD and neurodegenerative diseases plays an important role in several key pathophysiological mechanisms [36][37] .…”
Section: Effect Of Isorhamnetin On Aβ25-35 Induced Changes In Mrna Exmentioning
confidence: 99%
“…This was demonstrated by [ 11 C]-L-deprenyl using whole hemisphere autoradiography (38)(39)(40), epidemiology (41,42), morphology (43), as well as single-photon emission computed tomography (44). Such studies demonstrated that: i) MAO activity in platelets was significantly increased in patients with AD and acted as a marker of behavioral characteristics in dementia disorders (41,(45)(46)(47)(48); ii) there were early and persistent alterations in MAO-A and -B in the brains of patients with AD (49); iii) activated MAO led to cognitive dysfunction (50); iv) activated MAO destroyed cholinergic neurons and caused disorders of the cholinergic system (51); v) activated MAO contributed to the formation of amyloid plaques (13,14) and vi) activated MAO was associated with the formation of NFTs.…”
Section: Involvement Of Mao In Neurodegenerationmentioning
confidence: 99%
“…Compelling studies have shown that the involvement of MAO in AD and neurodegenerative diseases plays an important role in several key pathophysiological mechanisms (13,14). MAO-B has been proposed as a biomarker, whereas activated MAO-B leads to cognitive dysfunction, destroys cholinergic neurons, causes disorder of the cholinergic system and contributes to the formation of amyloid plaques.…”
Section: Introductionmentioning
confidence: 99%